Not Man Apart: Ecocentric Personification in the Works of Robinson Jeffers and John Steinbeck (American & British Studies Annual, 2012)
This essay probes the ecocentric dimension of the works of two quintessential California writers, Robinson Jeffers and John Steinbeck. While the representation of the Californian landscape in their writing has received much attention from critics, the non-anthropocentric vision often expressed in their works remained unnoticed for a long time. The primary objective of this essay is to examine the ways in which the authors use ecocentric personification to express their unconventional and sometimes even subversive views on the relationship between the human and the nonhuman world. The essay discusses different metaphors whose purpose is to affirm the unity and equality of all life forms. The representation of the earth as woman and woman as the earth is explored in particular depth, together with the (eco)philosophical implications of this strategy. It is also argued that ecocentric personification as a literary trope is used more competently by these two authors than by many other writers with Romantic leanings. It is the authors’ erudition in biology and ecology that enables them to imaginatively express ideas that are deeply grounded in holistic science. Jeffers and Steinbeck can thus be legitimately described as literary precursors of the influential Gaia theory that was postulated by James Lovelock as late as the 1970s.
Keywords: Robinson Jeffers; John Steinbeck; ecology; environmentalism; ecocentrism; ecofeminism; ecocentric personification